Brainstorming and Mind-mapping: Crucial Basic Skills Duet in Building Critical Thinking for Academic Composition - Christine Ike Budiana (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Academic writing in English has been a challenging basic skill for most English learners despite the levels of fluency the learners have. The range of struggle extends from the limited knowledge of the topic to the less practice in technical academic writing process. Although the challenges vary from one learner to another, there is a similar struggle indicated, particularly in starting the composition process. Brainstorming and mind-mapping have been commonly introduced as the initial phase for academic writing. Nevertheless, they are not as extensively practiced as the next steps of drafting. The next challenge in academic writing highlights the struggle in presenting logical flow of ideas to reflect the critical thinking of the writer. Interestingly, this struggle is closely related to the initial process of collecting and clustering ideas through brainstorming and mind-mapping. According to Pareto Principle, the 20% focus on building “vital few” – in this context is the basic skill – leads to 80% effective results of improvement. Thus, the extensive practice in brainstorming and mind-mapping as the basic skills in academic writing is believed to be crucial to support the whole composition process; particularly in developing the ideas and keeping the track of those ideas to present the critical and logical thinking of the writer.